Enhancing grammar learning motivation: a preliminary study on a mobile-assisted instruction tool / Aisyah Nazamud-din and Nur Aziela Aidit - Nazamud-Din, Aisyah; Aidit, Nur Aziela (Universiti Teknologi MARA, Kedah, 2024)
In the emerging field of language learning research, technology has played a significant role. However, recent empirical studies have highlighted a lack of attention to grammar learning, particularly in designing instructional materials and motivational frameworks for efficient mobile-assisted grammar learning tools. This paper presents the results of a preliminary study that aimed to investigate learner motivation when using a mobile-assisted tool for learning the Subject-Verb Agreement (SVA) rule in English language grammar and to examine the differences between male and female students in terms of their motivation when experiencing the tool. The study applied the Attention-Relevance- Confidence-Satisfaction (ARCS) model in the instructional design under the name, SVATHLON 2.0. It was a mobile-friendly Google site page that was developed to teach students SVA in a more engaged and gamified environment. The research employed a descriptive quantitative design, involving a questionnaire that was distributed to 111 undergraduate students who enrolled in a compulsory English language course for the semester 1 programme at a public university. The findings demonstrated that most students showed positive motivation after using SVATHLON 2.0 while learning SVA. The results of this preliminary study suggest that SVATHLON 2.0 could be an effective tool to enhance learner motivation, with positive responses from both male and female students. This study underscores the potential of gamified instructional materials to address the need for innovative and engaging approaches to grammar learning, particularly in the context of technology-assisted language education.